Identifying internship partner satisfaction in the chemistry teaching department at escola secundária geral pública 5 de maio de becora-academic year 2025 - Pedro Correia; Paulo Alves Cabral; Kristiani Kristiani; Adriano da Conceição Soares; António Referino Soares Ximenes; Policarpo Ornai Neto (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2026)
Academic internships constitute a fundamental component in the teacher training process at the Universidade Nacional Timor Lorosa’e (UNTL), as they provide students with opportunities to apply theoretical knowledge in real-world contexts and develop professional competencies. In this context, the Chemistry Teaching Department implements the internship program at Escola Secundária Geral Pública 5 de Maio de Becora, serving as a platform to offer students direct practical experiences and generate positive impacts on school partners. The main objective of this study was to identify the level of satisfaction among internship partners and analyze the factors influencing it, while providing recommendations to enhance the quality of future internship programs. This research employed a descriptive quantitative method. The study population consisted of 55 teachers who supervised the student interns. Data were collected using a five-point Likert scale questionnaire, based on 15 indicators for variable X (Pedagogical Practice II) and 15 indicators for variable Y (Satisfaction of Pedagogical Practice II Partners). The data were analyzed through descriptive statistics and Pearson correlation. The mean value of variable X (Pedagogical Practice II) was 62.22, while that of variable Y (Partner Satisfaction) was 59.69, reflecting a high level of satisfaction. Correlation analysis revealed a strong and positive relationship between variables X and Y, with a coefficient of r = 0.718 and a significance level of p < 0.001, indicating a substantial and meaningful association between interns’ competencies and partner satisfaction. The factors that contributed most to the level of satisfaction included preparation of materials, effective communication, responsibility, content mastery, and professional ethics. Internship partners also recommended conducting regular pre-internship orientations and strengthening communication between the department and partner schools. This study provides significant contributions for improving UNTL’s internship programs and may serve as a reference for future research in education, particularly in chemistry teaching. The obtained data offer a foundation for program development, as partner feedback determines both the validity and continuity of the program, supported by effective collaboration.